Global Development and Cooperation with China (Springer Nature, 2025)
This open access book draws on the insights and wisdom of representatives from a wide range of international organizations with a presence in China, leveraging their rich experience in their respective fields as well as their unique understanding of China’s development and its role in the world. In a world of increased tension between governments and a rise in regionalism, globally positioned non-governmental international organizations are key to keeping the lines of communication open. In addition to the United Nations and its affiliate organizations, a host of international organizations are ensuring that the world’s most pressing issues, in areas ranging from economics to education, are being discussed. This new book focuses on the latest trends in four major areas—global governance, trade and economics, science and technology, and culture and exchange—providing the reader with information on the latest developments in these areas with a special focus on China and its relevant contributions. It is hoped that this book will inspire deeper discussion and consideration of the issues we face as a global community and how non-governmental entities can play a stabilizing role in global communication and in exploring solutions to common challenges.